2022
DOI: 10.1155/2022/6339184
|View full text |Cite|
|
Sign up to set email alerts
|

Design Model of Cultural and Creative Products Using User Perception Demand Mining

Abstract: People are becoming more and more aware of the value of design throughout a product’s entire life cycle as a result of the fierce competition for industrial products that exists today. The life of a product involves its design, manufacture, sale, and use, and how well these links are managed determines the product’s positioning in terms of value in the eyes of consumers. The key to the functional integration of the design is monitoring the entire process and applying the user’s emotional needs. A useful tool f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Nowadays, the utilization of cultural identities and traditions in product design is widespread, especially in creating added value and distinctiveness (Hiranteeyakul and Thungsaku, 2022;Yang, 2022). Current craftsmanship designs draw inspiration from various cultural elements, and their distinctiveness has become a significant selling point for handicrafts and product designs (Arumdee and Joneurairatana, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the utilization of cultural identities and traditions in product design is widespread, especially in creating added value and distinctiveness (Hiranteeyakul and Thungsaku, 2022;Yang, 2022). Current craftsmanship designs draw inspiration from various cultural elements, and their distinctiveness has become a significant selling point for handicrafts and product designs (Arumdee and Joneurairatana, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is a key factor in promoting local culture and developing the tourist industry, as each location has unique qualities [8]. Natural cultural differences may partially compensate for a lack of inventiveness and regional growth in China's artistic and creative sectors [9,10].Cultural heritage encompasses the mental and bodily contributions of the local population to the long-term social and historical growth of an entire nation or region [11]. It is constantly enhanced established and enhanced [12].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%